A SWOT Analysis on the Implementation of the Yoghurt Marketing Strategy: A Case Study in the Malang, Indonesia - Nanang Febrianto; Ria Dewi Andriani; Manik Eirry Sawitri (Faculty of Animal Science, Universitas Brawijaya, 2023)
Milk as a farm product has a significant role in improving the quality of human resources through the intersection of protein and mineral needs. One of the dairy products is yogurt or probiotic fermented milk. Yoghurt is a processed milk food that is a valuable ingredient for the human body and contains high levels of protein, lactose, and lactic acid. This research is conducted to identify the company's internal and external environmental conditions and formulate business development strategies. The research methods are survey methods with data collection techniques through observation, interviews, and documentation. Research respondents are internal parties: the company leadership and the production section. Respondents from external parties are agents, consumers, competitors, and related agencies. Data analysis uses SWOT analysis. The results showed that the total average score of the IFE matrix was 2,353, and the EFE matrix was 2,587. An alternative formulation of S-O strategies by maintaining product quality and excellence to attract customers. W-O's strategy is to cooperate with investors to obtain investments. S-T strategy by doing marketing research. W-T strategy by promoting products that are more vigorous and effective.